Intra-ocular lens opacification in the anterior chamber leading to loss of vision in an adolescent - Chaudhry, Mrindu; Mundey, Keerti; Baisakhiya, Shikha; Sethi, Sumita (Nepalese Journal of Ophthalmology, 2014)
Objective: To report a rare case of intraocular lens (ACIOL) opacification in the anterior chamber in an adolescent and to discuss the possible mechanism of its occurrence and the ways of its prevention. Case: A 16-year-old male underwent cataract surgery for developmental cataract with placement of a foldable posterior chamber IOL in the anterior chamber. There was subsequent opacification of the IOL, which was replaced by a scleral fixated posterior chamber intraocular lens. The post-operative visual acuity improved to 6/18. Conclusion: The posterior chamber IOL implanted in the anterior chamber can get opacified possibly due to postoperative intraocular inflammation. DOI: http://dx.doi.org/10.3126/nepjoph.v6i1.10780   Nepal J Ophthalmol 2014; 6 (2): 102-104